IMPLEMENTASI KEBIJAKAN PEMBELAJARAN BUDAYA MELAYU RIAU DALAM KURIKULUM PENDIDIKAN KOTA PEKANBARU TAHUN 2023-2024 - Septia, Rindiyani; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to analyze the implementation of the local content learning policy of Riau Malay Culture (BMR) in the curriculum in Pekanbaru City in the 2023-2024 academic year. The study focuses on policy implementation, using the George C. Edward III policy implementation model which includes communication, resources, disposition, and bureaucratic structure. The research method used is qualitative. Data were collected through interviews with relevant parties such as the Education Office, the Riau Malay Traditional Institution (LAMR) of Pekanbaru City, school principals, and teachers. The results of the study indicate that the implementation of the BMR policy faces various obstacles, including lack of socialization and limited human resources, as well as ineffective coordination between the Education Office and LAM Pekanbaru City. The implications of this study are the need to improve communication, provide adequate resources, strengthen teacher capacity, and improve coordination between institutions to ensure the effective and sustainable implementation of the BMR policy. Keywords: Policy Implementation, Riau Malay Culture, Curriculum, Education.